A Study of Broad Emission Line and Doppler Factor Estimation for Fermi Blazars - Chen, Guohai; Zheng, Zepeng; Zeng, Xiangtao; Zhang, Lixia; Xiao, Hubing; Liu, Xiang; Cui, Lang; Fan, Junhui (The Astrophysical journal. Supplement series, 2024)
In this work, we obtained a sample of 979 Fermi blazars with broad emission lines, including 701 objects collected from published works and 278 objects developed in this work. For the 278 objects, we made a crossmatch from three catalogs, the Fermi Large Area Telescope Fourth Source Catalog (4FGL), the Sloan Digital Sky Survey, and the Large Sky Area Multi-Object Fiber Spectroscopic Telescope, and calculated the broad-line region (BLR) luminosity. Then, we estimated the Doppler factor and studied the correlations between the BLR luminosities and the γ -ray luminosities, the synchrotron peak frequency ( ν p ), and Doppler factor ( δ ) for the whole sample. Our analyses and discussions came to the following main conclusions: For the 278 blazars, their BLR luminosity (log L BLR ) ranges from 40.44 to 45.45 erg s −1 , with a mean value of 43.39 erg s −1 . The Doppler factor ranges from δ = 0.45 to δ = 88.52, with a mean value of 12.99 for the 979 Fermi blazars, which is consistent with the results in the literature. Both the BLR luminosity and the Doppler factor exhibit positive correlations with the γ -ray luminosity. The BLR luminosity is anticorrelated with synchrotron peak frequency, implying a Compton cooling. A line of log L BLR = 1.58 log ν p − 19.46 separating BL Lacertae objects and flat-spectrum radio quasars was obtained in the diagram of log L BLR against log ν p using a machine-learning method. Based on the analysis of the equivalent width and the Doppler factors, we proposed five changing-look blazar candidates.